An update on the diagnosis and management of tic disorders - Ishita Desai; Niraj Kumar; Vinay Goyal (Annals of Indian Academy of Neurology, 2023)
Tic disorders (TDs) are a group of common neuropsychiatric disorders of childhood and adolescence. TDs may impact the physical, emotional, and social well-being of the affected person. In this review, we present an update on the clinical manifestations, pathophysiology, diagnosis, and treatment of TDs. We searched the PubMed database for articles on tics and Tourette syndrome. More than 400 articles were reviewed, of which 141 are included in this review. TDs are more prevalent in children than in adults and in males than in females. It may result from a complex interaction between various genetic, environmental, and immunological factors. Dysregulation in the cortico-striato-pallido-thalamo-cortical network is the most plausible pathophysiology resulting in tics. TD is a clinical diagnosis based on clinical features and findings on neurological examination, especially the identification of tic phenomenology. In addition to tics, TD patients may have sensory features, including premonitory urge; enhanced and persistent sensitivity to non-noxious external or internal stimuli; and behavioral manifestations, including attention deficit hyperactivity disorders, obsessive-compulsive disorders, and autism spectrum disorders. Clinical findings of hyperkinetic movements that usually mimic tics have been compared and contrasted with those of TD. Patients with TD may not require specific treatment if tics are not distressing. Psychoeducation and supportive therapy can help reduce tics when combined with medication. Dispelling myths and promoting acceptance are important to improve patient outcomes. Using European, Canadian, and American guidelines, the treatment of TD, including behavioral therapy, medical therapy, and emerging/experimental therapy, has been discussed.